Analisis Penerapan PPH Pasal 24 Pada PT. Telkom Indonesia Tbk - Nurita Pasaribu; Hotman Siboro; Desry R Tarigan; Putri Kemala Dewi Lubis (Departement of Mathematics Education, 2024)
This study aims to analyze the implementation of Income Tax (PPh) Article 24 at PT Telkom Indonesia Tbk, one of the largest multinational companies in Indonesia. PPh Article 24 is implemented to prevent double taxation of income earned from abroad, so that companies can credit taxes paid abroad against taxes owed in Indonesia. This study uses a qualitative descriptive approach with data obtained from PT Telkom Indonesia's annual report and related scientific articles. The results of the study indicate that the implementation of PPh Article 24 has a significant impact on the company's financial performance, especially on the decline in net profit due to international tax burdens. To mitigate this impact, PT Telkom utilizes the Double Taxation Avoidance Agreement (P3B) and collaborates with international tax consultants to ensure that all tax obligations can be met efficiently and in accordance with international tax provisions. This study provides important insights into effective tax strategies for multinational companies operating in multiple jurisdictions and the importance of a deep understanding of international tax policies.